PENERAPAN SUPLEMENTASI ASAM AMINO METIONIN DALAM PAKAN SEBAGAI UPAYA PERCEPATAN PRODUKSI PEM BUDIDAYA LELE SANGKURIANG DESA TAMBAKSARI, KECAMATAN ROWOSARI, KABUPATEN KENDAL - Rachmawati, Diana; Elfitasari, Tita; Yuniarti, Tristiana (Universitas Mataram, 2025)
The success of fish farming is largely determined by the availability of quality feed that not only contains protein that meets the needs of the fish, but also contains a complete amino acid profile. The problem faced by catfish farmers Sangkuriang Sido Makmur Tambaksari Village, Rowosari District, Kendal District, which is a partner of the community service activity of the Community Superior Commodity Strengthening (PKUM) scheme is the still low efficiency of feed utilization so that feed costs are high, almost 60% of the total production costs. This is because soybeans as a source of vegetable protein in feed have limited methionine amino acid content. One effort to overcome partner problems is to apply methionine amino acid supplementation in feed to improve feed quality. The method of community service activities of the PKUM scheme consists of several stages, namely socialization, training, application of technology, mentoring and evaluation, and sustainability. The purpose of this PKUM scheme community service activity is to assist partners in solving problems so that feed utilization efficiency increases, fish growth increases, feed costs decrease and partner income increases. From the results of the PKUM scheme community service activities, it shows that the increase in the efficient value of feed utilization is 75%, fish growth is 4.2%/day, feed costs decrease to 50% of the total production costs, Sangkurian catfish production increases to 2,050 kg/cultivation cycle and partner income increases to Rp.8,750.-00/cultivation cycle. The results of the PKUM scheme community service activities can be concluded that the application of methionine amino acid supplementation in feed can increase the efficiency of feed utilization, the growth of Sangkuriang catfish, reduce feed costs and increase the income of partner members